Seksualitas: Media Pemuasan Hasrat (Perspektif Kosmologi Hindu) - Kadek Kadek Agus Wardana; Kadek Ayu Kristini Putri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Sexuality is a component of an individual's personal identity that is inseparable and develops and matures throughout an individual's life. Sexuality is not the same as sex. Sexuality is the interaction of biological factors, personal psychology, and the environment. Biological function refers to an individual's ability to give and receive pleasure and to reproduce. Psychological sexual identity and self-concept refer to an individual's inner understanding of sexuality such as self-image, identification as male or female, and learning of masculine or feminine roles. In writing this article, the method used is literature study by entering keywords on google.scholar.com and various other literature to support the references of this article. In addition, several articles and/or books related to this theme also support the completion of this article. Hindu cosmology is the concept of the creation of the universe and its contents, no less important in the concept of cosmology is sexuality and spirituality which are important and integrated dimensions, where through human sexuality, individuals can experience a direct erotic relationship with God and perform a new creation and continuously evolved to give birth to new genes/generations.